No evidence for association of the CD40, CD40L and BLYS polymorphisms, B-cell co-stimulatory molecules, with Brazilian endemic Plasmodium vivax malaria - Capobianco, Marcela P. [UNESP]; Cassiano, Gustavo C. [UNESP]; Furini, Adriana A. C.; Storti-Melo, Luciane M.; Pavarino, E' rika C.; Galbiattid, Ana L. S.; Fraga, Valéria D.; Conceição, Luciana M.; Couto, Vanja S. C.; Coutof, Álvaro A. R. A.; Machado, Ricardo L. D. [UNESP] (Oxford University Press (OUP), 2013)
Background: Plasmodium vivax is the most prevalent malaria species in Brazil. The parasite-host coevolutionary process can be viewed as an 'arms race', in which adaptive genetic changes in one are eventually matched by alterations in the other. Methods: Following the candidate gene approach we analyzed the CD40, CD40L and BLYS genes that participate in B-cell co-stimulation, for associations with P. vivax malaria. The study sample included 97 patients and 103 controls. We extracted DNA using the extraction and purification commercial kit and identified the following SNPs: 21C.T in the CD40 gene, 2726T.C in the CD40L gene and the 2871C.T in the BLyS gene using PCR-RFLP. We analyzed the genotype and allele frequencies by direct counting. We also compared the observed with the expected genotype frequencies using the Hardy-Weinberg equilibrium. Results: The allele and genotype frequencies for these SNPs did not differ statistically between patient and control groups. Gene-gene interactions were not observed between the CD40 and BLYS and between the CD40L and BLYS genes. Overall, the genes were in Hardy-Weinberg equilibrium. Significant differences were not observed among the frequencies of antibody responses against P. vivax sporozoite and erythrocytic antigens and the CD40 and BLYS genotypes. Conclusions: The results of this study show that, although the investigated CD40, CD40L and BLYS alleles differ functionally, this variation does not alter the functionality of the molecules in a way that would interfere in susceptibility to the disease. The variants of these genes may influence the clinical course rather than simply increase or decrease susceptibility. © Royal Society of Tropical Medicine and Hygiene 2013. All rights reserved.
Keywords: BLYS; CD40; CD40L; Malaria; Plasmodium vivax; Single nucleotide polymorphism; B cell activating factor; CD40 antigen; CD40 ligand; DNA; erythrocyte antigen; allele; antibody response; B lymphocyte; comparative study; controlled study; disease association; DNA extraction; DNA purification; gene frequency; gene interaction; gene linkage disequilibrium; genotype; human; major clinical study; Plasmodium vivax malaria; single nucleotide polymorphism; sporozoite